PELATIHAN DAN PEMBINAAN WARGA BINAAN PEMASYARAKATAN DI LAPAS PALEDANG BOGOR UNTUK MEWUJUDKAN PERLINDUNGAN HAK ASASI MANUSIA - Suhartini, Endeh; Roestamyi, Martin; Mulyadi; Maryam, Siti (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
This study aims to determine the form of training and coaching for inmates at the Paledang Prison, Bogor. The main purpose of a correctional institution is to provide guidance for inmates based on the system, institution, and method of coaching as the final part of the criminal justice system in the criminal justice system. In this study, the author uses the empirical method with data collection techniques of observation, interviews and questionnaires. The training and coaching of the inmates who were held at the Bogor Paleadang Penitentiary was running effectively. The guidance provided is divided into two, namely personality development and independence development.